Examination of Nutritional Information of Athletes in Different Olympic Branches - Hakan Yarar,; Mehmet Can Akgul,; Muhammed Enes Akgul,; Tugce Cig, (Journal of Educational Issues, 2024)
Nutrition is one of the most important factors for a healthy life, growth, development, appropriate body weight, defense against diseases, and sportive performance. The person’s age, gender, daily physical activity status, and before, after, and during training and competitions should be fed appropriately. Since the performance in athletes takes place by expending physical effort, the supply of necessary energy plays a key role in performance. Purpose: This study aims to examine athletes’ nutritional information in different Olympic sports branches. 313 athletes with an average age of 22.53 years, a body weight of 68.87 kg, a height of 174.44 cm, and an average sports age of 8 years, active in different Olympic sports branches, participated in the study. In the study, the data, the “Athlete Nutrition Knowledge Scale” was used. The arithmetic mean and standard deviations, descriptive properties, and percentage distribution frequencies of the obtained data were determined, and the SPSS 20 package program was used for all statistical analyses. Important findings were obtained within the scope of the study; Protein is the main source of energy used by muscles during exercise in 54.8% of athletes. When 50.2% of people want muscle gain, the basic dietary change required is to increase the amount of protein in the diet. 48.4% of vegetarian athletes can meet their protein requirements without using protein supplements. 45.8% Fruits and Vegetables are the best sources of calcium. Milk, Yogurt, and Cheese with 49.2% are the best sources of magnesium. 57.2% of Athletes A physically fit person with an adequate diet can improve his performance by consuming more vitamins and minerals. 66.2% of athletes should take vitamin C as a routine supplement by athletes. 50% of athletes test the purity and safety of all supplements before the sale. As a result of the study, when the above findings were examined, it was concluded that the knowledge of the athletes interested in the Olympic branches is not at the desired level and that they have partially wrong nutrition information. It is thought that it is necessary to increase nutritional knowledge.